VERTICAL DISTRIBUTIONS OF TEMPERATURE, SALINITY AND GEOSTROPHIC FLOW ALONG 155°E AND 170°W IN THE SOUTHERN OCEAN IN DECEMBER 1968-FEBRUARY 1969 (EXTENDED ABSTRACT) (Ninth Symposium on Polar Biology) - ナガノブ, ミキオ; NAGANOBU, Mikio (National Institute of Polar Research, 1987)
P(論文) departmental bulletin paper